Ventajas del aprendizaje cooperativo para el logro de conductas adaptativas de las personas con discapacidad intelectual - SchwarzAguayo, Ledda (2011)
lt is about the cooperative learning advantages which contribute to boost learning and abilities development of a person with intellectual disability in a cooperative work which stimulates the objective achievement, developing a positive attitude of an integrative environment among thestudents